A material delivery system built on Internet of Things and the role of libraries. Issue 1 (4th July 2019) - Hou, Hanping; Yang, Jianliang; Chen, Yong; Yu, Mingli
Abstract : Purpose: After the occurrence of natural disasters, the rapid and accurate delivery of geo-afforestation is the key to emergency rescue and is the fundamental solution to the "last mile" problem. It provides technical support for the territorial rapid and accurate delivery. The paper aims to discuss this issue. Design/methodology/approach: Through literature and theoretical research, combined with the research experience of scholars, the qualitative research method is adopted. The paper establishes a three-dimensional analysis framework, including disaster predictability, resource availability and transport accessibility, and proposes the integrated delivery triangular technical framework, including integrated monitoring analysis, the territorial virtual public storage and transportation. Findings: Based on the analysis of the factors affecting the effectiveness of emergency delivery, the paper establishes a three-dimensional analysis framework, including disaster predictability, resource availability and transport accessibility, and proposes the integrated delivery triangular technical framework, including integrated monitoring analysis, the territorial virtual public storage and transportation. The triangular technical characteristics and functions of emergency delivery are studied, providing theoretical basis and technical support for effective rescue and emergency planning. Originality/value: The territorial emergency delivery refers to the process of rapid and accurate delivery without relying on external territorial supplies. The paper establishes a three-dimensional analysis framework, including disaster predictability, resource availability and transport accessibility, and proposes the integrated delivery triangular technical framework, including integrated monitoring analysis, the territorial virtual public storage and transportation.